KADAR HEMOGLOBIN PENDERITA TUBERKULOSIS PARU YANG MENJALANKAN TERAPI OBAT ANTI TUBERKULOSIS DI PUSKESMAS PANCUR BATU KABUPATEN DELI SERDANG 2019 - Paska Ramawati Situmorang (Elisabeth Health Jurnal, 2020)
ntroduction: Tuberculosis (TB) is a contagious infectious disease caused by mycobacterium tuberculosis. Indonesia is a country with the third largest case of pulmonary tuberculosis in the world. The purpose of this study is to determine the description of hemoglobin levels in patients with pulmonary tuberculosis who are undergoing anti-tuberculosis therapy in Pancur Batu Health Center, Deli Serdang Regency.Method:The research method is descriptive with the study population being all patients with pulmonary tuberculosis who are undergoing anti-tuberculosis therapy, and a sample of 21 respondents. Result: Based on the results of the analysis, it is known that there is an effect of green color therapy on changes in the level of student anxiety in facing exams.Discussion: The results of the study based on age obtained that most respondents aged between 60-72 years were 8 respondents (38.1%), most respondents were male as many as 14 respondents (66.7%) with abnormal hemoglobin levels 12 respondents (87,1%). The conclusion of this study is the results of research based on age there are the most respondents aged 60-72 years, male sex with more hemoglobin levels that are not normal (anemia).